Direct measurement of proinsulin in human plasma by the use of an insulin-degrading enzyme - Kitabchi, Abbas E. (1971)
A method has been described for the direct measurement of proinsulin in human plasma. The method makes use of an insulin-degrading enzyme designated “insulin-specific protease (ISP)”, which is obtained from rat skeletal muscle. Under the conditions used, this enzyme rapidly degrades insulin and insulin-like polypeptides to nonimmunoassayable components, whereas proinsulin and proinsulin cleaved at position B(54,55) are not appreciably affected. The incubation of plasma with ISP results in the disappearance of insulin, but not proinsulin, as demonstrated by column chromatography. Immunoassay of the plasma, therefore, before and after incubation, determines the values for the total immunoreactive substance (TIR) and for immunoreactive proinsulin (IRP), respectively. The values obtained for proinsulin levels are reproducible and compare closely with the more complicated column fractionation methods. Proinsulin responses were studied in four normal subjects and one patient with an insulinoma after a glucose load. Fasting proinsulin levels varied widely in the normal subjects, and the levels rose more slowly than TIR levels after glucose. IRP levels in the patient with an insulinoma were very high and fell to normal after removal of the tumor. The ISP method, therefore, appears to be suitable for the direct, accurate, and rapid determination of proinsulin and proinsulin-like materials in human plasma.